On the little-known comb-footed spider genus Audifia Keyserling, 1884 (Araneae, Theridiidae) - Rodrigues, Everton Nei Lopes (Zootaxa, 2024)
The spider genus Audifia Keyserling, 1884 currently comprises three described species, two species from Brazil and one from Guinea-Bissau and Congo. In this paper the male of an Audifia species is illustrated for the first time and new records are presented for the genus. Audifia laevithorax Keyserling, 1884 is recorded for the first time from Bolivia, and new record from Amazonia, Brazil is reported. The male Audifia semigranosa Simon, 1895 is described and illustrated for the first time and new record from Brazil is presented.